AVANCES EN INTERACCIÓN HOMBRE – MÁQUINA - Ramírez - Icaza., Fernando (2019)
This article emphasizes research on different forms of interaction between man - machine, which will widely spread out in a not too distant future through physical robots, virtual robots, or orders issued by the human brain processed by electrodes capable of capturing the energy of the biochemical process between neurons and thus read human thought. Robots during Man – Machine interaction must constantly make decisions. Therefore, when building knowledge bases it is important to consider the following steps: analysis of data, analysis of the representation of information based on taxonomic criteria, identification of axioms, suggested protective mechanism of axioms, inference mechanism suggestion, evaluation of formal systems, recommendation of formal systems, recommendation of the most convenient and expressive formal system for the representation of each of the axioms, recommendation to the team of software engineers of the most appropriate mechanism for incorporating axioms & rules. Finally, it draws conclusions and reflections of the author on this new paradigm of Computer Sciences.